Associations between coping strategies and insomnia: a longitudinal study of Japanese workers. Issue 2 (29th September 2021) - Otsuka, Yuichiro; Itani, Osamu; Matsumoto, Yuuki; Kaneita, Yoshitaka
Abstract: Study Objectives: Coping with stress is important because stress disturbs sleep. However, only a few longitudinal studies have investigated the association between coping and insomnia. We examined whether individuals with insomnia symptoms used more maladaptive coping strategies than individuals without insomnia symptoms, and evaluated the association between insomnia symptoms and coping strategies. Methods: In this prospective cohort study, Japanese workers were enrolled and observed over a 2-year period. During both years, self-administered questionnaires on coping and insomnia symptoms were administered. Coping was assessed using the Brief-Coping Orientation to Problems Experienced, and insomnia symptoms were examined using the Athens Insomnia Scale. Generalized estimating equation modeling identified the effects of coping strategies on insomnia severity. Results: In total, 1358 of 1855 workers at baseline were followed up. Individuals with insomnia symptoms showed a higher use of maladaptive coping strategies and less use of humor and instrumental support than individuals without insomnia symptoms. Active coping, humor, emotional support, and instrumental support were negatively associated with insomnia severity. In contrast, venting, substance use, behavioral disengagement, and self-blame were positively associated with insomnia severity. Conclusions: This study showed that individuals with insomnia symptoms use both adaptive and maladaptive coping strategies and are more likely to use maladaptive strategies than individuals without insomnia symptoms. In the future, interventions focused on educating people about adaptive coping strategies should be conducted to determine whether coping strategies may prevent insomnia symptoms.